The Effectiveness of Interactive Jigsaw on Students’ Reading Ability and Motivation - Septiani, Septiani; Thohir, Lalu; Saputra, Agus; Apgrianto, Kurniawan (Journal of Authentic Research, 2025)
This study aims to examine the effectiveness of the Interactive Jigsaw Method in improving reading skills and learning motivation among students at Baiturrahman Mahmudi Bebuak Islamic Junior High School. The main problem faced is the low reading ability and motivation of students. The Interactive Jigsaw Method was chosen as a solution because it encourages cooperative learning. This study uses a quantitative. The pre-test results showed that students’ reading ability were very low, with 50% of students in the low category and the rest in the poor and failing categories. However, after implementing the Jigsaw Method, there was a significant improvement in the post-test. Of the 34 students, 58.82% achieved the excellent category, 32.35% the good category, and the rest were adequate. Statistical analysis using a paired t-test showed a t-test value of 4.246, well above the critical t-table value (2.032), with a significance level of less than 0.01. This proves that the method is significantly effective in improving reading skills. This method also has a positive impact on student motivation. (80.3%) of students had high motivation, while (14.7%) students had low motivation. These findings confirm that the Interactive Jigsaw Method successfully increased students’ motivation to learn reading. It can be concluded that the Interactive Jigsaw Method is significantly effective in improving students’ reading ability and learning motivation.